2010
DOI: 10.1080/00150193.2010.489853
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dielectric Studies of NaNbO3-A0.5Bi0.5TiO3(A-Li,Na,K) Solid Solutions

Abstract: Structural and dielectric studies of NaNbO 3 solid solutions with ternary perovskites A 0.5 Bi 0.5 TiO 3 (A-Li, Na, K) have shown that while the evolution with x of the temperature dependence of dielectric permittivity, phase transition temperatures and structural parameters for (100-x)NaNbO 3 -(x)Na 0.5 Bi 0.5 TiO 3 system are typical of the group II NaNbO 3 -based solid solutions, the properties of (100-x)NaNbO 3 -(x)A 0.5 Bi 0.5 TiO 3 (A-Li, K) systems combine the features typical of both group II and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…Noteworthy, the phase transition between ferroelectric and paraelectric becomes more diffuse with the increase in BBKT content, indicating the disturbance of ferroelectric long‐range order and formation of polar nano‐regions due to cation disorder in A‐ and B‐sites. This similar phenomenon also existed in other NaNbO 3 ‐based systems including NaNbO 3 –Bi 0.5 Li 0.5 TiO 3 , NaNbO 3 –Na 0.5 Bi 0.5 TiO 3 , and NaNbO 3 –Bi(Zn 0.5 Ti 0.5 )O 3 …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Noteworthy, the phase transition between ferroelectric and paraelectric becomes more diffuse with the increase in BBKT content, indicating the disturbance of ferroelectric long‐range order and formation of polar nano‐regions due to cation disorder in A‐ and B‐sites. This similar phenomenon also existed in other NaNbO 3 ‐based systems including NaNbO 3 –Bi 0.5 Li 0.5 TiO 3 , NaNbO 3 –Na 0.5 Bi 0.5 TiO 3 , and NaNbO 3 –Bi(Zn 0.5 Ti 0.5 )O 3 …”
Section: Resultssupporting
confidence: 78%
“…This similar phenomenon also existed in other NaNbO 3 -based systems including NaNbO 3 -Bi 0.5 Li 0.5 TiO 3 , NaNbO 3 -Na 0.5 Bi 0.5 TiO 3 , and NaNbO 3 -Bi(Zn 0.5 Ti 0.5 ) O 3 . [39][40][41] As a matter of fact, most pyroelectric materials include AC-coupled detectors which work at relatively low frequency. 42 Thus, the frequency stability of pyroelectric materials is crucially important to practical application.…”
Section: Temperature and Frequency Dependence Of Dielectric Characteristicsmentioning
confidence: 99%
“…However, the antiferroelectric phase is prevalent at room temperature. 12−16 To realize the stable existence of the ferroelectric phase in NN-based ceramics, researchers introduced LiTaO 3 , 17 BaTiO 3 , 12,18,19 and (K 0.5 Bi 0.5 )TiO 3 20,21 as the second component to obtain NN-based piezoelectric ceramics with a stable ferroelectric phase. Zeng et al found that the antiferroelectric phase of NN-based ceramics was transformed to ferroelectric orthorhombic (O) phase after the addition of a small amount of BT.…”
Section: Introductionmentioning
confidence: 99%
“…NaNbO 3 ceramics exhibit a ferroelectric phase with electric field and possess piezoelectric properties ( d 33 ∼ 20 pC/N). However, the antiferroelectric phase is prevalent at room temperature. To realize the stable existence of the ferroelectric phase in NN-based ceramics, researchers introduced LiTaO 3 , BaTiO 3 , ,, and (K 0.5 Bi 0.5 )­TiO 3 , as the second component to obtain NN-based piezoelectric ceramics with a stable ferroelectric phase. Zeng et al.…”
Section: Introductionmentioning
confidence: 99%